2018
DOI: 10.1177/1179069518798628
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Mechanisms That Depend on Dopamine and Serotonin in Caenorhabditis elegans Interact With the Antipsychotics Risperidone and Aripiprazole

Abstract: The neurotransmitters dopamine and serotonin participate in specific behavioral neuromuscular mechanisms in the nematode Caenorhabditis elegans. Dopamine is involved in the gentle touch response and serotonin in the pharyngeal pumping rate. In its genome, the worm presents genes encoding dopamine and serotonin receptors orthologous to those of human genes. Risperidone and aripiprazole are a class of drugs known as atypical antipsychotics commonly used to treat schizophrenia, bipolar disorder, and irritability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Future natural history studies of NGLY1 deficiency should focus on catecholamine insufficiency as a potential driver or axis of pathophysiology. The effects of aripiprazole in worms depends on catecholamine pathway genes (Osuna-Lugue et al, 2018). In flies, aripiprazole was shown to reduce the levels of an aggregated polyglutamine-expanded mutant protein in a model of Machado-Joseph disease, or spinocerebellar ataxia type 3 (Costa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Future natural history studies of NGLY1 deficiency should focus on catecholamine insufficiency as a potential driver or axis of pathophysiology. The effects of aripiprazole in worms depends on catecholamine pathway genes (Osuna-Lugue et al, 2018). In flies, aripiprazole was shown to reduce the levels of an aggregated polyglutamine-expanded mutant protein in a model of Machado-Joseph disease, or spinocerebellar ataxia type 3 (Costa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding behavior was reported to be inhibited in C. elegans supporting current study due to the effects of a class of APDs however risperidone was not evaluated for pharyngeal pumping assay in this study ( Donohoe et al, 2006 ). Our results show significant inhibitory effects in pharyngeal pumping mechanism compared to modest effects due to Risperidone (150 μM) and aripiprazole (300 μM) treatment observed in C. elegans ( Osuna-Luque et al, 2018 ). This could be explained due to variation in exposure duration and use of liquid culture assay for drug exposure which requires lesser concentration by increasing bioavailability ( Zheng et al, 2013 ).…”
Section: Discussionmentioning
confidence: 55%
“…A recent study with risperidone and aripiprazole revealed serotonin and dopamine-dependent behavioral alterations in pharyngeal pumping mechanism and gentle touch response wherein C. elegans N2 strain was exposed to 150 μM and 300 μM concentrations respectively ( Osuna-Luque et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…As C. elegans is one of the easiest and cheapest multicellular eukaryotic organism to apply precise genome editing to, the choice of this simple nematode for studying PD biology provides fast, cheap in vivo modelling with great translational potential (21,29,51), as discussed throughout this review. C. elegans functional studies of other Mendelian PD genes and their orthologues, including PINK1, Parkin, ATP13A2 and DJ-1, or PD risk genes, such as GBA1, have proven the strength of this invertebrate model, highlighting highly conserved functions of these genes and proteins in cellular pathways disrupted in PD, including mitophagy, lysosomal degradation and α-synuclein pathology (49,134,177,(265)(266)(267)(268)(269)(270)(271)(272)(273). Complex functional interaction of all of these PD proteins and LRRK2 have been described in PD patient samples and in animal models, which supports the idea that LRRK2 is a master regulator of cellular trafficking and quality control pathways, maintaining a crosstalk of a multitude of cellular processes and reflects on the high complexity of Parkinson's pathology (13,(274)(275)(276)(277).…”
Section: Lrrk2 and Beyond: The Potential Of C Elegans For Functional Modelling Of Parkinson's Gwas Candidate Genesmentioning
confidence: 99%
“…C. elegans present a range of PD relevant behavioural and organismal phenotypes to characterise and test, as outputs of gene function, which range from specific dopaminergic neuron attributable behaviours (36,(48)(49)(50), in vivo microscopy (51), to organismal responses to environmental stressors (35), as summarised in Figure 2.…”
mentioning
confidence: 99%